POTENSI PENINGGALAN ARKEOLOGI CANDI GONDOSULI SEBAGAI DESTINASI WISATA EDUKASI - Naufal Raffi Arrazaq (UHN IGB Sugriwa Denpasar, 2023)
The purpose of this study is to analyze the various findings of archaeological relics at Gondosuli Temple and analyze the concept of utilizing archaeological relics at Gondosuli Temple as an educational tourist destination. Qualitative methods are used as the basis for research related to the use of archaeological relics of Gondosuli Temple as an educational tourist destination. The results showed that the variety of archaeological relics found in Gondosuli Temple consists of component of temple stones, Yoni, Nandi statues, and Gondosuli Inscriptions. The archaeological relics can be developed as an educational tourist destination by combining the potential that exists in Gondosuli Village in the form of natural and cultural resources. The supporting natural resources around Gondosuli Temple includes Mount Sumbing, agricultural land, and rivers. The cultural potentials are crafts, arts, and traditions. Existing archaeological relics can be made into educational tour packages by combining the potentials in Gondosuli Village. Tourism development is carried out using tutorial learning methods and exploration activities. Flow of visits could be designed on Gondosuli Temple, the Gondosuli Inscription, Mount Sumbing, river crossings, and community settlements. Keywords: archaeological relics, Gondosuli temple, educational tourism